The Early Years Child Well-Being and the Role of Public Policy - Berlinski, Samuel; Schady, Norbert (Springer Nature, 2015)
Economics, Development Economics, Social Policy, Children, Youth and Family Policy, Sociology, Childhood and Youth, Development, Children and Youth, International Economics